Behavioural Observations of Adult-Child Pairs at a Pelican Crossing: A Case Study in Kuala Lumpur - Ahmad Termida, Nursitihazlin (International Journal of Integrated Engineering, 2019)
Pedestrian accidents are a serious problem in Malaysia, especially child pedestrians. Over the past decade, pedestrian fatalities in Malaysia were ranked third after car and motorcycle related fatalities, in which 40% of the casualties involved children aged 6 to 10 years old. To date, however, little are known about children’s behaviour in actual traffic environments, and their behaviours when they are accompanied by adults while crossing the roads. The present study is intended to fill this gap by observing the behaviours of 98 adult-child pairs as they crossing the roads on Pedestrian Light Controlled Crossing (Pelican) type at an urban signalised intersection in Kuala Lumpur. Eight behaviours were coded: crossing in the crosswalk, stopping at the kerb, parents giving oral instructions to the child, pressing the button, waiting for the ‘Green man’, looking at both directions before crossing, holding hands, and walking (not running) while crossing. The results show that adults set a good example to the children on how to cross the Pelican crossing safely, but they are not taking this advantage to educate their children regarding the crossing behaviour. They also seem to show that 10-year old children can be trusted to conduct safe crossing behaviour, and/or can be educated on how to cross the roads safely. The only gender difference to emerge revealed that girls are more likely to walk while crossing as compared to boys. Several age differences are significantly affect children crossing behaviours.